1988
DOI: 10.1055/s-2007-1010813
|View full text |Cite
|
Sign up to set email alerts
|

Flight Effects on Plasma Levels of Free Fatty Acids, Growth Hormone and Thyroid Hormones in Homing Pigeons

Abstract: Significant increases in circulating levels of free fatty acids (FFA) and growth hormone (GH), were observed in homing pigeons after a flight of 48 km, lasting 60-80 min. No significant change in plasma levels of thyroxine (T4) and triiodothyronine (T3) was observed. Nor was there any change in T3/T4 ratio. The increase in plasma FFA is attributed to the increased release into circulation of at least one adipokinetic hormone, GH. It may be concluded that in free sustained homing flight under normal weather con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
2
10
3
Order By: Relevance
“…We chose these distances because given a flight speed of around 60-70·km·h -1 , we expected pigeons released from Arezzo to fly for more than 2·h. This is important because within about 1-2·h of flight, the metabolism of pigeons switches from carbohydrates to fats (John et al, 1988).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose these distances because given a flight speed of around 60-70·km·h -1 , we expected pigeons released from Arezzo to fly for more than 2·h. This is important because within about 1-2·h of flight, the metabolism of pigeons switches from carbohydrates to fats (John et al, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies on homing pigeons have shown that none of the investigated blood parameters (e.g. uric acid, haematocrit, osmolality, Na + and K + ) show drastic changes during flights lasting around 1·h (John et al, 1988;Bordel and Haase, 1993;George and John, 1993). During flights of about 1-2·h, the metabolism of pigeons switches from using carbohydrates to fats in order to produce energy (John et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the earlier study (Viswanathan et al 1987) with homing pigeons, it was also observed that there were increases in plasma levels of glucose, lactate, adrenaline and noradrenaline after a flight of 48 km lasting 60-80 min. In a recent investigation, John, Viswanathan, George and Scanes (1988) reported significant increases in plasma levels of FFA and growth hormone (GH) in homing pigeons after a flight of the same distance and duration. In the present study with homing pigeons we have ventured to investigate post-flight changes in blood levels of glucagon which is known to be a powerful adipokinetic hormone in birds (Langslow and Hales 1971).…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established that during sus tained muscular activity, birds metabolize fat as the chief fuel [49][50][51][52][53], Marked increases in postflight plasma levels of triglycerides, free fatty acids (FFA), glucagon and growth hor mone (GH) have been reported in homing pigeons [23,54], Increases in plasma levels of FFA and GH have also been shown in pigeons subjected to heat stress and dehydration [55], The observation that plasma levels of AVT are increased in heat-stressed domestic fowl [ 14] suggests that AVT may have a lipolytic action besides its well-known role as an anti diuretic hormone. That AVT has indeed an adipokinetic action has been demonstrated in pigeon in vivo and also in in vitro experi ments [56] using pigeon adipose tissue slices [57], an action that may be mediated by cAMP [58], In this context, it may be men tioned that the release of AVT from the poste rior lobe in migratory birds prior to migration has been considered as an important event in the initiation of Spring migratory activity [59].…”
Section: Discussionmentioning
confidence: 99%